Unleashing nature's defense: potent antimicrobial power of plant extracts against oral pathogens and Streptococcus mutans biofilms - Hickl, Joachim; Argyropoulou, Aikaterini; Al-Ahmad, Ali; Hellwig, Elmar; Skaltsounis, Alexios Leandros; Wittmer, Annette; Vach, Kirstin; Karygianni, Lamprini (Frontiers in Oral Health, 2024)
ObjectivesThe increasing demand for alternatives to antibiotics against resistant bacteria has led to research on natural products. The aim of this study was to analyze the antimicrobial and antibiofilm activity of 16 Mediterranean herb extracts.Materials and methodsThe extracts were analyzed using High Performance Thin Layer Chromatography. The minimum inhibitory concentration and minimum bactericidal concentration of the extracts from Achillea taygetea, Cistus creticus ssp. creticus, Cistus monspeliensis, Lavandula stoechas, Mentha aquatica, Mentha longifolia, Origanum vulgare, Phlomis cretica, Rosmarinus officinalis, Salvia sclarea, Satureja parnassica, Satureja thymbra, Sideritis euboea, Sideritis syriaca, Stachys spinosa, and Thymus longicaulis were determined against eight oral bacteria and fungus Candida albicans. Microtiter plate test was conducted to evaluate the antibiofilm activity against Streptococcus mutans.ResultsOverall, all tested extracts efficiently suppressed the growth of obligate anaerobic bacteria. When applied at concentrations ≥0.15 mg/ml, the extracts exhibited moderate to high antibiofilm activity comparable to that of chlorhexidine (CHX) against S. mutans. Interestingly, R. officinalis (MIC: 0.01–0.06 mg/ml) and O. vulgare (MIC: 0.04–1.25 mg/ml) demonstrated the highest antibacterial activity against oral bacteria. Additionally, R. officinalis and L. stoechas significantly inhibited S. mutans biofilm formation at 0.15 mg/ml.ConclusionsThe tested plant extracts can be considered as alternative natural antimicrobial and antibiofilm agents.Clinical relevanceMediterranean herb extracts show promise as natural alternatives to combat oral bacteria and biofilm formation, offering potential new therapies for infectious oral diseases in the context of antibiotic resistance.